Quasar viscosity crisis. (February 2018) - Lawrence, Andy
Recent observations of extreme variability in active galactic nuclei have pushed standard viscous accretion disk models over the edge. I suggest either that some kind of non-local physics dominates accretion disks, or that the optical output we see comes entirely from reprocessing a central source.